Welfare of the laying hen (Poultry science symposium, 2004)
This book contains 32 edited papers from the 27th Poultry Science Symposium of the World's Poultry Science Association (UK) held in Bristol, UK, in July 2003. Topics covered include: welfare issues, perception and cognition; behaviour, health and disease, stockmanship and the environment; handling, slaughter and transport; and perspectives of consumers and producers.